2004
DOI: 10.1111/j.1365-2362.2004.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplasia‐associated autoimmunity: clinical and pathophysiologic concepts

Abstract: Myelodysplastic syndrome ( MDS), an acquired clonal disorder of haemopoietic progenitor cells, is characterized by haemopoietic insufficiency associated with cytopenias, leading to serious morbidity plus the additional risk of leukaemic transformation. In MDS an acquired insult to the haemopoietic stem cell leads to impaired differentiation and myelodysplasia. However, there is increasing evidence that the marrow failure of MDS is immune-mediated. A model of MDS pathophysiology suggests that transformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 95 publications
1
56
0
3
Order By: Relevance
“…20 In this study we investigated anti-erythroid cell autoimmunity both in peripheral blood and bone marrow and describe, for the first time, the presence of anti-erythroblast autoimmunity in half of RA and RARS patients. Only half of these patients show signs of hemolysis, although their mean values of reticulocyte number, unconjugated bilirubin and LDH concentration are higher, and haptoglobin levels lower than those of patients without evidence of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…20 In this study we investigated anti-erythroid cell autoimmunity both in peripheral blood and bone marrow and describe, for the first time, the presence of anti-erythroblast autoimmunity in half of RA and RARS patients. Only half of these patients show signs of hemolysis, although their mean values of reticulocyte number, unconjugated bilirubin and LDH concentration are higher, and haptoglobin levels lower than those of patients without evidence of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Although reported more commonly for lymphoproliferative neoplasms (Zintzaras et al, 2005;Ekstrom Smedby et al, 2008), increased risks in persons with autoimmune conditions have also been noted for myeloid malignancies, including AML and CML (Zheng et al, 1993;Askling et al, 2005b). Autoimmune conditions, which occur commonly in patients with MDS (Voulgarelis et al, 2004), have also been reported to precede MDS (Dalamaga et al, 2002). Using data from the Surveillance Epidemiology and End Results (SEER)-Medicare Assessment of Hematopoietic Malignancy Risk Traits (SMAHRT) study, we investigated whether autoimmune conditions were associated with subsequent risks of AML, CML, MDS and MPDs.…”
mentioning
confidence: 99%
“…There is a recognized association between autoimmune phenomenon, such as connective tissue disorders and systemic vasculitic disorders with the presence of MDS. [2][3][4][5] Clinical and laboratory findings have suggested an autoimmune mediated component to the pancytopenia and bone marrow (BM) failure seen in MDS [6][7][8][9] with observations of increased oligoclonal expansion of T cells and possible cytotoxic T-cellmediated suppression of Hematopoietic progenitors. [10][11][12] Immunosuppressive therapy has been shown to induce sustained hematological responses in a subset of patients with MDS.…”
Section: Introductionmentioning
confidence: 99%